Analysis of Islamic Bank Marketing Strategies in Increasing Easy Wadiah Savings Products at BSI KCP Rungkut 1 - Mohammad Diki Kurniawan; Rukhul Amin; Dian Berkah (UNIVED Press, 2025)
This study aims to analyze marketing strategies in improving Easy Wadiah Savings products at Bank Syariah Indonesia (BSI) KCP Rungkut 1. This study uses a qualitative approach with a case study method, where data is obtained through direct interviews with the bank as well as related documentation and literature. The results of the study indicate that BSI KCP Rungkut 1 has implemented a marketing strategy based on a marketing mix (7P), which includes products, prices, places, promotions, processes, human resources, and physical evidence. Strategies such as direct reward programs, QRIS cashback promotions, customer education, and community approaches have proven effective in attracting customer interest, especially micro segments such as housewives, students, and MSMEs. The main obstacles faced are low sharia financial literacy and competition with conventional banks. Therefore, increasing community-based literacy and optimizing local digital marketing strategies are important recommendations to strengthen the competitiveness of Easy Wadiah Savings products. This study is expected to be a reference for sharia financial institutions in designing more effective and sustainable marketing strategies.